Reforming antitrust - Devlin, Alan (Alan James) (Cambridge : Cambridge University Press, 2021)
Industrial consolidation, digital platforms, and changing political views have spurred debate about the interplay between public and private power in the United States and have created a bipartisan appetite for potential antitrust reform that would mark the most profound shift in US competition policy in the past half-century. While neo-Brandeisians call for a reawakening of antitrust in the form of a return to structuralism and a concomitant rejection of economic analysis founded on competitive effects, proponents of the status quo look on this state of affairs with alarm. Scrutinizing the latest evidence, Alan J. Devlin finds a middle ground. US antitrust laws warrant revision, he argues, but with far more nuance than current debates suggest. He offers a new vision of antitrust reform, achieved by refining our enforcement policies and jettisoning an unwarranted obsession with minimizing errors of economic analysis.
Competition law's role -- Antitrust-fact, fiction, and the unknown --The missing link-concentration and market power -- Warning signs in the economy-has competition declined? -- A liberal call to arms, but is deconcentration the answer? -- Testing the Neo-Brandeisian vision --Taking a finger off the scale-revisiting decision theory -- Rethinking the consumer -welfare standard -- The antitrust evolution -- Key recommendations.
Title from publisher's bibliographic system (viewed on 20 Aug 2021).
Keywords: Antitrust law; Law reform; Competition, Unfair